2018
DOI: 10.1093/nar/gky270
|View full text |Cite
|
Sign up to set email alerts
|

Improving RNA nearest neighbor parameters for helices by going beyond the two-state model

Abstract: RNA folding free energy change nearest neighbor parameters are widely used to predict folding stabilities of secondary structures. They were determined by linear regression to datasets of optical melting experiments on small model systems. Traditionally, the optical melting experiments are analyzed assuming a two-state model, i.e. a structure is either complete or denatured. Experimental evidence, however, shows that structures exist in an ensemble of conformations. Partition functions calculated with existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 52 publications
5
42
0
Order By: Relevance
“…buffer species and pH, salt identity and concentrations, polyamines, solvent, molecular crowding agents, temperature and equilibration time) and type of assay used to measure relative stabilities (24–26,40,48–50). Similar study-to-study variations have been observed for the stability of D•D–D base triplets and base pairs in dsRNA, both of which vary greatly depending on neighboring base triplets or base pairs (46,51,52). These results reinforce the importance of experimentally testing each computationally predicted triple helix, given the number of factors that can influence the overall stability of a triple helix.…”
Section: Discussionsupporting
confidence: 66%
“…buffer species and pH, salt identity and concentrations, polyamines, solvent, molecular crowding agents, temperature and equilibration time) and type of assay used to measure relative stabilities (24–26,40,48–50). Similar study-to-study variations have been observed for the stability of D•D–D base triplets and base pairs in dsRNA, both of which vary greatly depending on neighboring base triplets or base pairs (46,51,52). These results reinforce the importance of experimentally testing each computationally predicted triple helix, given the number of factors that can influence the overall stability of a triple helix.…”
Section: Discussionsupporting
confidence: 66%
“…One source of systemic error is that optical melting experiments are analyzed assuming two-state behavior. Our previous work shows that this leads to errors in the Watson-Crick parameters (Spasic et al 2018). Another source of systematic error is that the nearest neighbor model is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…The U exc in Equation (1) represents excluded volume interactions between two CG beads, and the P, C, and N beads are treated as spheres with van der Waals radii (r) of 1.9 Å, 1.7 Å, and 2.2 Å, respectively. The U bp , U bs , and U cs in Equation (1) are the base-pairing (between Watson-Crick and wobble base pairs), base-stacking (between nearest-neighbor base pairs), and coaxial stacking (between two discontinuous neighbor helices) interactions, respectively, and the strength of them was derived from sequence-dependent thermodynamic parameters and the corresponding experimental data (Xia et al, 1998;Spasic et al, 2018). The last term U el in Equation ( 1) is an electrostatic potential corresponding to electrostatic interactions between phosphate groups (a charge of -e for each P bead at its center), which are ignored by most existing predictive models for RNA 3D structures (Hajdin et al, 2010;Rose et al, 2011;Shi et al, 2014b;Schlick and Pyle, 2017).…”
Section: The Cg Structure Model and Force Fieldmentioning
confidence: 99%